THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, WORK ENVIRONMENT AND INCENTIVES ON MORALE - Amalia, Frisca Fika; Prayekti, Prayekti (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Abstract Work morale is a feeling that is present in someone when carrying out their work so that they do their work feeling happy and can complete their work quickly and responsibly. The aim of this research is to determine the influence of transformational leadership, work environment and incentives on work morale at the Head Office of Waroeng Special Sambal